Oceanography of the Arabian Sea during Southwest monsoon season Part I: Thermal structure - SASTRY , J. S.; D'SOUZA, R. S. (MAUSAM, 1970)
The thermal structure of the Arabian Sea (between 5° and 20°N) during the southwest monsoon season, 1963 is presented through a series of vertical sections and horizontal charts showing the temperature distribution at surface and subsurface levels. Charts showing the thickness or the surface layer, the extent of the thermocline and its variation with latitude and the topography of certain isothermal surfaces are also included, the studies revealed that the large spatial variations in surface temperature exceeding 11°C are due to processes such as radiation imbalances over the region, intense upwelling off the coasts of Somali and Arabia and a complex intermingling of various water masses. The thickness of surface layer has been found to vary from about 10 m to more than 120 m, it has been found that the near surface circulation affects the development of the surface layer considerably, The nature and the variation of the thermocline is investigated, The thermal characteristics of the intermediate and bottom waters are also presented.